Cracking the relation between mass and 1P-star fraction of globular clusters: III. Initial distributions of in situ and ex situ clusters - Parmentier, Geneviève (The astrophysical journal, 2025)
Galactic globular clusters consist of two main stellar populations, the pristine (1P) and polluted (2P) stars. The fraction of 1P stars in clusters, F1P, is a decreasing function of the present-day cluster mass, mprst. The information about cluster formation it contains has yet to be unlocked. Paper I demonstrated that the observed distribution (mprst, F1P) of Galactic globular clusters can result from a pristine-star fraction that is inversely proportional to their birth mass, mecl. This relation was then calibrated with a fixed stellar mass threshold for 2P-star formation, mth, i.e., F1P = mth/mecl. We now estimate the masses minit of Galactic globular clusters as they start their long-term gas-free evolution in the Galaxy and we map their behavior in the (minit, F1P) space. Several dissolution timescales are tested (with and without primordial mass segregation), each yielding its own initial cluster distribution (minit, F1P). The (minit, F1P) distributions are mapped according to cluster origin, with the emphasis on the Disk, Low-Energy and Gaia-Enceladus cluster groups of D. Massari et al. All three initial distributions (minit, F1P) are more compact than their present-day counterparts since dynamical evolution scatters clusters in the F1P versus cluster-mass space. The Disk initial distribution is the tightest one and potential reasons for this are discussed. Its power-law representation allows us to generalize the initial mass threshold of Paper I and prompts us to represent the cluster (mass, F1P) distribution in a log-log space. No evidence is found suggesting that, initially, the pristine-star fraction of globular clusters depends on their metallicity on top of their mass.
Veröffentlicht: 12. Juni 2025
Gesehen am 15.10.2025